2021
DOI: 10.1088/1361-6560/abfa34
|View full text |Cite
|
Sign up to set email alerts
|

Optimising use of 4D-CT phase information for radiomics analysis in lung cancer patients treated with stereotactic body radiotherapy

Abstract: Purpose . 4D-CT is routine imaging for lung cancer patients treated with stereotactic body radiotherapy. No studies have investigated optimal 4D phase selection for radiomics. We aim to determine how phase data should be used to identify prognostic biomarkers for distant failure, and test whether stability assessment is required. A phase selection approach will be developed to aid studies with different 4D protocols and account for patient differences. Methods . 186 features w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…The counterintuitive result of Region 1 is explained by considering the mean EQD2 dose inside each of the regions identified by the dose parameter (Supplementary Figure 13). In region 1, the median value is 55 Gy with range 74-92 Gy, which is significantly higher than 9 Gy (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) in R2 and 14 Gy (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) in R3. Considering the difference in dose scales, a large SD in this region would not lead to underdosage of microscopic disease.…”
Section: Confounding Investigationmentioning
confidence: 87%
See 1 more Smart Citation
“…The counterintuitive result of Region 1 is explained by considering the mean EQD2 dose inside each of the regions identified by the dose parameter (Supplementary Figure 13). In region 1, the median value is 55 Gy with range 74-92 Gy, which is significantly higher than 9 Gy (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) in R2 and 14 Gy (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) in R3. Considering the difference in dose scales, a large SD in this region would not lead to underdosage of microscopic disease.…”
Section: Confounding Investigationmentioning
confidence: 87%
“…Planning four-dimensional CT (4D-CT) scans [described in Davey et al. ( 18 )] and 3D dose distributions were available for all patients. Patients received a dose of 54 Gy in 3 fractions, or 60 Gy in 5 or 8 fractions, with further planning details included in Supplementary Material , Section 1.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown that tumor motion can alter the radiomic feature space in discrete ways 21,22,27 . However, whether motion-associated variations are deterministic, capturing true changes in tumor composition, or stochastic, representing "noise" to be dampened remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although the documented instability in the classical radiomic feature space created by tumor motion has been established 21,22,27 , it remains unclear if these variations are clinically meaningful. Moreover, motion-related variations in some radiomic features may not be relevant to DL models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation